2021
DOI: 10.1111/jfpp.16003
|View full text |Cite
|
Sign up to set email alerts
|

The synergistic effects of aloe vera gel and modified atmosphere packaging on the quality of strawberry fruit

Abstract: The aim of this study was to evaluate modified atmospheric packaging containing 500 ppm cinnamon essential oil, aloe vera concentrated gel (1:3 with distilled water), calcium lactate, and ascorbic acid on the shelf life of strawberry. Acidity, antioxidant activity, soluble solids, phenolic compound, anthocyanin content, vitamin C content, weight loss, firmness, color, gas composition as well as microbial quality were determined during 15 days of shelf life. According to the results, the antioxidant activity wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 44 publications
0
27
0
1
Order By: Relevance
“…These results are comparable with the results of coating with A. vera gel and cinnamon EO in modified atmosphere packaging of strawberry. A reduction in microbial populations during storage was observed but there was no change observed in the mold and yeast counts until day 10 of storage; however, on day 15, a decrease in the microbial load was noticed [89]. At the end storage, the fruits treated with A. vera gel 40% and lemongrass EO recorded a lower microbial count than the fruits that underwent all other treatments.…”
Section: Microbiological Analysismentioning
confidence: 88%
“…These results are comparable with the results of coating with A. vera gel and cinnamon EO in modified atmosphere packaging of strawberry. A reduction in microbial populations during storage was observed but there was no change observed in the mold and yeast counts until day 10 of storage; however, on day 15, a decrease in the microbial load was noticed [89]. At the end storage, the fruits treated with A. vera gel 40% and lemongrass EO recorded a lower microbial count than the fruits that underwent all other treatments.…”
Section: Microbiological Analysismentioning
confidence: 88%
“…However, in an active modified atmosphere packaging (MAP)/MAS system, the interaction between the chemical absorber (sachets) and stored product performs some desired function other than just providing a barrier to the external environment and helps to improve the quality and safety of perishable fresh produce by maintaining the optimum gas concentration for longer period (Charles et al, 2003). Esmaeili et al (2021) also reported that the incorporation of cinnamon essential oil, aloe vera concentrated gel, calcium lactate and ascorbic acid in MAP of strawberry can effectively preserve its quality attributes for longer period of time. Thus, an active MAS system becomes highly adaptable and more convincing during bulk storage, handling, distribution and transportation of fresh produce.…”
Section: Novelty Impact Statementmentioning
confidence: 99%
“…The customer judges the quality according to several sensorial factors such as firmness, appearance [9], and other related chemical properties such as vitamin C content and total soluble solids [10]. Storage can increasesome biological activities such as growth of the bacteria, molds, and yeasts [11]. Moreover, several studies reported that stored cucumbers have been associated with some microbial contaminations such as Salmonella, being contaminated during post-harvest processes [12,13].…”
Section: Introductionmentioning
confidence: 99%